ANALYZING ENGLISH VOWEL SOUNDS PRODUCED BY SECOND GRADE STUDENTS OF SMA N 1 SUKASADA IN ACADEMIC YEAR 2014 / 2015 - ., I Gusti Agung Anom Maruti Putra; ., Drs. I Wayan Suarnajaya,MA., Ph.D.; ., Drs. Asril Marjohan,MA (Jurnal Pendidikan Bahasa Inggris undiksha, 2013)
Tujuan dari penelitian ini adalah untuk menganalisis suara vocal bahasa inggris yang di ucapkan oleh siswa-siswa kelas XI di SMA Negeri 1 Sukasada. peneliti menunjuk enam belas siswa yang terbaik dalam pelajaran bahasa inggris dari empat kelas. Siswa â€“ siswa mengucapkan dua belas suara vocal dalam bahasa inggris ialah [ i ], [ ï‰ ], [ e ], [ ïƒŽ ], [ ï‘ ], [ ï‚« ], [ ïƒƒ ], [ u ], [ ï• ], [ ï‚ ], [ ï‚ ], and [ ï ]. Peneliti menganalisis menggunakan software speech analyzer dan software Cambridge Learner Dictionary untuk menentukan suara yang benar. Hasil dari penelitian ini adalah dari dua belas vocal dalam bahasa inggris, siswa â€“ siswa hanya dapat mengucapkan dua suara vocal dalam bahasa inggris diantaranya bahasa inggris vocal [ e ], [ É™ ] dan [ u: ], karena mereka terpengaruh oleh bahasa ibunya (first language). This research aimed at to analyze english vowel sounds produced by Second Grade Students of SMA Negeri 1 Sukasada. The researcher chooses sixteen best students in English from four classes. The students produces twelve english vowel sounds such as [ i ], [ ï‰ ], [ e ], [ ïƒŽ ], [ ï‘ ], [ ï‚« ], [ ïƒƒ ], [ u ], [ ï• ], [ ï‚ ], [ ï‚ ], and [ ï ]. The researcher analyzes the studentsâ€™ vowel sounds and identifies how the students produced those english vowel sounds are. In this study, the researcher use speech analyzer software to analyze the data and Cambridge advance learner dictionary software to determine the correct sounds. The result of this research showed from twelve english vowel sounds, the students were able to pronounced three English vowel sound correctly, there are English vowel [ e ], [ É™ ] and [ u: ], because they still influenced by their mother tongue.keyword : English Sound, English Vowel Sounds